Flow and heat distribution analysis of different transformer sub-stations - Hasini H.; Shuaib N.H.; Yogendran S.B.; Toh K.B. (2023)
This paper describes CFD investigation on the flow and heat transfer in transformers at different sub-station buildings. The analysis aimed to determine the cooling capability of the existing transformer building employing natural ventilation system to dissipate heat sufficiently when new dry-type transformer operating under full load condition is used. The transformer and building models were developed based on the actual transformer configuration in operation at three different locations in Malaysia. The calculation was carried out on three different types of sub-stations namely stand-alone, attach-to-building and underground. The effect of natural ventilation speed and building volume on the transformer surfaces temperature are also investigated. It was predicted that the existing sub-station configuration is able to dissipate heat produced from the dry type transformer by using its natural ventilation system regardless of the sub-station types. However, the smallest building case shows relatively high surrounding temperature. Published under licence by IOP Publishing Ltd.